A Hybrid Algorithm of ACO and Delete-Cross Method for TSP - Wu Junqiang; Ouyang Aijia (2012 International Conference on Industrial Control and Electronics Engineering, 2012)
A hybrid ant colony algorithm (HACO) which is containing ant colony algorithm (ACO) and delete-cross method which is used to speed the convergence of local search is presented for the shortcoming that the convergence speed of ant colony algorithm (ACO) is a bit slow. The experiment results have indicated that HACO has better performance than six versions of ant colony algorithm (ACO) on searching the shortest paths, error and robustness in the test of typical TSPs.